2022
DOI: 10.3390/ijerph19169780
|View full text |Cite
|
Sign up to set email alerts
|

Housing Security and Settlement Intentions of Migrants in Urban China

Abstract: A huge gap remains in the urbanization rate between China and developed countries, although China has experienced a rapid growth in urbanization rate over the last decade. Critical to the future growth of urbanization is how to increase the settlement intentions of migrants. This study uses land supply for security housing as an exogeneous shock to the supply of security housing in the near future to explore how housing security is associated with intentions to settle down in destination cities of the migrant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Existing studies have shown that most rural migrants choose to live in impoverished neighborhoods in urban centers or areas bordering urban and rural areas, with very poor living conditions [ 1 3 ]. Recent studies revealed that stable housing can promote the long-term settlement of rural migrants in cities and towns by improving the social integration of migrants [ 4 , 5 ]. The closer the rural migrants live to the urban area and the closer they are to the living space of urban residents, the easier they are to form an urban identity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies have shown that most rural migrants choose to live in impoverished neighborhoods in urban centers or areas bordering urban and rural areas, with very poor living conditions [ 1 3 ]. Recent studies revealed that stable housing can promote the long-term settlement of rural migrants in cities and towns by improving the social integration of migrants [ 4 , 5 ]. The closer the rural migrants live to the urban area and the closer they are to the living space of urban residents, the easier they are to form an urban identity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…19,20 In past decades, China experienced one of the world's fastest urbanization and infrastructure development. 21,22 However, limited research is available exploring the modification role of various dimensions of city development in the association between hydrological conditions and dengue fever incidence. Given the increasing dengue fever incidence and the extended geographic distribution in the context of climate change, it is necessary to explore the modification of the JAMA Network Open | Environmental Health association between hydrological conditions and dengue fever incidence by multidimensional city features.…”
Section: Introductionmentioning
confidence: 99%
“…For example, abundant health care resources may improve the emergency response capacity for dengue fever treatment, while high population density and mobility may increase the frequency of the mosquito-person transmission chain . In past decades, China experienced one of the world’s fastest urbanization and infrastructure development . However, limited research is available exploring the modification role of various dimensions of city development in the association between hydrological conditions and dengue fever incidence.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of social factors and human capital factors, social identity [9], social ties [10], social integration [11], and even vocational-skills training [12] all have the significant effects on the settlement intentions of migrants. Finally, some residence factors, like housing security or homeownership, also have a significant effect on the settlement intentions of migrants [13,14].…”
Section: Introductionmentioning
confidence: 99%